Vonoprazan-Based Regimen Is More Useful than PPI-Based One as a First-Line Helicobacter pylori Eradication: A Randomized Controlled Trial - Masafumi Maruyama; Naoki Tanaka; Daisuke Kubota; Masayuki Miyajima; Takefumi Kimura; Koujiro Tokutake; Ryujiro Imai; Toru Fujisawa; Hiromitsu Mori; Yoshiaki Matsuda; Shuichi Wada; Akira Horiuchi; et al. (Canadian Journal of Gastroenterology and Hepatology)
Background. A new agent, potassium-competitive acid blocker vonoprazan (VPZ) has potent acid-inhibitory effects and may offer advantages over conventional H. pylori eradication therapies. We aimed to compare the eradication rate between VPZ-based treatment and PPI-based one. Methods. This randomized controlled trial was designed to assign 141 patients with H. pylori-positive gastritis to VPZ group (VPZ 20 mg, amoxicillin 750 mg, and clarithromycin 200 or 400 mg twice daily for 7 days) or PPI group (rabeprazole 20 mg or lansoprazole 30 mg, amoxicillin 750 mg, and clarithromycin 200 or 400 mg twice daily for 7 days). Primary endpoints were eradication rates and adverse events. Results. Seventy of 72 patients in VPZ group and 63 of 69 patients in PPI group completed the treatment after 7 days. The eradication rate was significantly higher in VPZ group than PPI group by intention-to-treat analysis (95.8% versus 69.6%, P=0.00003, 95% confidence interval [CI] 88.3-99.1% versus 57.3-80.1%) and per-protocol analysis (95.7% versus 71.4%, P=0.0002, 95% CI 88.0-99.1% versus 58.7-82.1%). The incidence of adverse events was not different between the groups (26.3% in VPZ group versus 37.7% in PPI group, P=0.15). Conclusion. VPZ-based regimen is more useful than that PPI-based regimen as a first-line H. pylori eradication therapy.